Driving of underground SAW temperature sensor system using magnetic energy and its wireless measurement system development - Kim, Si Hyeok; Lee, Keekeun (Transactions of the Korean Institute of Electrical Engineers, 2019)
A wireless underground sensor system was developed based on magnetic antennas and surface acoustic wave (SAW) resonator to monitor temperature variations around buried utilities. A~250 MHz magnetic antenna generates a SAW along the piezoelectric substrate, and the returned SAW energy owing to the reflection bars on the sensor is reconverted to magnetic flux by the sensor’s interdigital transducer (IDT) and subsequently transmitted to a reader via magnetic antenna. By observing changes in the center frequency of the SAW sensor with temperature, we were able to monitor the underground temperature variations in real time. Temperature sensor was fabricated on a 128o YX LiNbO3. In soil testing, a long readout distance was observed. The temperature sensors provided stable performance in terms of underground temperature changes, soil type, and soil compactness. The sensitivity and linearity for the sensor was 0.3 MHz/℃ and 0.96, respectively.
Keywords: Magnetic antennas; Piezoelectric substrates; Saw temperature sensors; Surface acoustic wave resonators; Surface acoustic waves; Underground temperature; Wireless communications; Wireless measurement system; Magnetic antenna; Magnetic field; Resonator; Surface acoustic wave; Temperature sensor; Underground wireless communication